Catalogue of Highly Important Egyptian, Western Asiatic, Greek and Roman Antiquities. Sotheby’s Sale Catalogue. Day of Sale: 29th Nov. 1965 - Anonymus, A. (1965)
spez. p. 22, no. 47: Head of Gudea; p. 25 no. 48: Western Anatolian White Marble Figurine; no. 49: . . . Marble Head; p. 26, no. 52: Susa Pottery; no. 55: Luristan Bronze Pin; p. 27, no. 56: Luristan Iron Axe; no. 57: Luristan Bronze Harness Ring; no. 58 and 59: Luristan Bronze Pin; p. 28, no. 60: Luristan Funerary Talisman; no. 61: Luristan Horse’s Bit; no. 62: Luristan Axehead; p. 29, no. 65: Large Bowl, Hacılar; nos. 67-69: Sumerian Animal Figurines; p. 30, no. 70: Proto-Elamite Amulet; no. 71: Syrian Bronze Figure of a Ram; no. 71A: Neo-Вabylonian Chalcedony Macehead.